Aproximación a la figura de Julio César y su relación con Hispania - Martínez Mera, Josefa (Estudios humanísticos. Geografía, historia y arte, 2001)
In this work we have an approach to the figure of Julius Caesar throught his historiography and also throught his political action in Roman Spain during the Civil War. Caesar has attracted historian attention because of his personality and authority.